Environment Adaptable Nanocomposite Organohydrogels for Multifunctional Epidermal Sensors. Issue 6 (17th January 2022) - Yu, Yang; Xie, Fengjin; Gao, Yanan; Gao, Xinpei; Zheng, Liqiang
Abstract: Electronic skins, as a revolution in artificial intelligence, have drawn intensive attention in smart prosthetic devices, wearable health monitors and intelligent robot manufacturing. Conductive hydrogels as building blocks have been highlighted in artificial skin research. Nevertheless, the main challenges of hydrogel‐based electronics are poor temperature tolerance, weak mechanical robustness and limited stretchability. Herein, an organohydrogel is fabricated with "soft and hard" synergistic networks by combining "soft" polyacrylamide (PAM) and catechol‐modified hyaluronic acid (HA‐CA) polymer network with "hard" Laponite nanoparticles. The obtained organohydrogels exhibit excellent environment‐adaptability, super stretchability (>8000%), superior adhesion to various substrates, superfast self‐healing efficiency (<10 s), excellent conductivity (63 mS m −1 ) even at −0 °C and good biocompatibility. These outstanding properties render the organohydrogels as epidermal flexible sensors. The fabricated sensor exhibits wide strain sensing range (0−300%), super sensitivity (gauge factor, GF = 8.38−133.94) which can effectively detect and discriminate various human activities, and maintain their functions at extremely cold conditions. This versatile organohydrogel offers a platform for practical application of flexible wearable devices in extreme environments. Abstract : An environment adaptable and ultrastretchable organohydrogel with "soft and hard" synergistic networks for multifunctional epidermal sensors is shown.